PENETAPAN KADAR FLAVONOID EKSTRAK ETANOL BUAH MENGKUDU (Morinda citrifolia L.) - Ayuningtyas, Nurista; Ayu Ina, Ayu Ina; Setyopuspito, Anastasia; Trisina, Jessica; Mardiyono, Amida Kesya (Jurnal Farmasi & Sains Indonesia, 2023)
Noni fruit has traditionally been used for treatment due to its secondary metabolite content, one of which is flavonoid. This research aims to determine the secondary metabolite content of 96% ethanol extract of noni fruit and total flavonoids in the extract. The research method was conducted experimentally. Noni fruit extract was obtained by maceration method, phytochemical screening was performed to determine the content of secondary metabolites in qualitatively. Total flavonoids were analyzed by colorimetric method with quercetin as standard. Quercetin levels were measured by Spectrophotometry Uv-Vis. The results obtained yield of noni fruit extract 3.60% + 0.31. Phytochemical screening of noni fruit extract contains flavonoids, alkaloids, tannins, steroids, and saponins. The quercetin standard curve equation obtained y = 0.0067 x - 0.0148 with r = 0.9959. The result of total flavonoids in ethanol extract of noni fruit was 0.166% + 0.004.